Pengembangan Media Pembelajaran Video Animasi pada Materi Siklus Air Kelas IV Sekolah Dasar Negeri 74 Pontianak Barat - Adelia Risti; Siti Halidjah; Dyoty Auliya Vilda Ghasya (Journal on Education, 2023)
This study aims to develop animated video learning media that is valid for use by grade IV elementary school students on water cycle material. This type of research is development research by adopting the Borg and Gall model by taking 4 steps from 10 existing steps, namely, (1) Preliminary studies and information gathering, (2) Data collection, (3) Product design, (4) Design validation. The data obtained is mixed data, namely quantitative data obtained from the results of the questionnaire assessment of expert validators and practitioners as well as qualitative data that shows the level of validity of the product developed. The level of media validity is based on the results of the assessment by 1 media expert and 1 material expert. The results of the assessment from media experts obtained a percentage of 93.7% with valid criteria and the results of the assessment from material experts obtained a percentage of 90% with valid criteria.